The Influence of Intellectual Capital and Firm Size on Firm Value with ROA as an Intervening Variable in Sinar Mas Group Companies Listed on the IDX - M. Falah H.R. N.S.T; Heny Triastuti Kurnianingsih; Lusi Elviani Rangkuti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the influence of Intellectual Capital and Firm Size on Firm Value, with Return on Assets (ROA) as an intervening variable, in Sinar Mas Group companies listed on the Indonesia Stock Exchange (IDX). Methodology: This research employed a quantitative approach using path analysis through two regression models. Findings: The results indicate that Intellectual Capital and Firm Size have a positive and significant effect on ROA. Furthermore, Intellectual Capital, Firm Size, and ROA are proven to have a positive and significant effect on Firm Value. ROA also serves as a mediating variable that strengthens the indirect influence of Intellectual Capital and Firm Size on Firm Value. These findings suggest that profitability plays a crucial role in increasing the company's market value and bridging the relationship between internal company characteristics and firm value.